Laparoscopic Removal of Modified Vertical Uterine Compression Sutures due to Postoperative Focal Pain - Suzuki, Toshifumi (Surg J (N Y), 2020)
Previously we reported laparoscopic removal of compression sutures due to uterine ischemia and related pain, which has two of the difficult aspects: (1) maneuvering the curved needle to perform compression suturing in the narrow surgical field, and (2) distinguishing between the threads of the cesarean section wound sutures versus the vertical compression sutures during removal, as the threads are the same white color. We performed vertical compression sutures for intrapartum hemorrhage with total placental previa, and modified both the needle type and the color of the thread used for uterine compression sutures during cesarean section. After the operation, we performed successful laparoscopic removal of compression sutures for postoperative focal pain. Changing the needle type and color helped to perform operations. The present case supports the concept that the laparoscopic removal of uterine compression suturing is useful for controlling pain in cases where general analgesics are ineffective.